Solvothermal synthesis of nanoscale BaTiO3 in benzyl alcohol–water mixtures and effects of manganese oxide coating to enhance the PTCR effect. Issue 2 (12th December 2022) - Zhang, Min; Caldwell, Thomas; Hector, Andrew L.; Garcia-Araez, Nuria; Falvey, Joseph
Abstract : Phase pure nanocrystalline BaTiO3 prepared via a solvothermal synthesis and effects of manganese oxide coating to enhance the PTCR effect. Abstract : A solvothermal method using various benzyl alcohol/water solvent mixtures has been used to synthesise phase pure nanocrystalline BaTiO3 samples with varying particle sizes in the range of 11–139 nm. The crystallite/particle size of BaTiO3 shows an overall decrease as the benzyl alcohol percentage increases, especially at higher percentages (≥80%) of benzyl alcohol. The decrease in crystallite/particle size can be attributed to the increased viscosity of the solvent mixture when raising the percentage of benzyl alcohol. A manganese oxide coating applied to the BaTiO3 surface had a negligible impact on its microstructure and morphology, but significantly enhanced the observed positive temperature coefficient of resistance. This research has been carried out to allow the development of smaller BaTiO3 particles for use in new battery, capacitor and thermistor technologies, whilst maintaining the PTCR property of the material that is typically observed in larger particle sizes.